Remote Ischemic Preconditioning To Reduce Contrast-Induced Nephropathy: A Randomized Controlled Trial. Issue 4 (October 2015) - Menting, T.P.; Sterenborg, T.B.; de Waal, Y.; Donders, R.; Wever, K.E.; Lemson, M.S.; van der Vliet, J.A.; Wetzels, J.F.; SchultzeKool, L.J.; Warlé, M.C.
Abstract : Background: Despite the increasing use of pre- and post-hydration protocols and low osmolar instead of high osmolar iodine containing contrast media, the incidence of contrast induced nephropathy (CIN) is still significant. There is evidence that contrast media cause ischemia reperfusion injury of the renal medulla. Remote ischemic preconditioning (RIPC) is a non-invasive, safe, and low cost method to reduce ischemia reperfusion injury. The aim of this study is to investigate whether RIPC, as an adjunct to standard preventive measures, reduces contrast induced acute kidney injury in patients at risk of CIN. Methods: The RIPCIN study is a multicenter, single blinded, randomized controlled trial in which 76 patients at risk of CIN received standard hydration combined with RIPC or hydration with sham preconditioning. RIPC was applied by four cycles of 5 min ischemia and 5 min reperfusion of the forearm. The primary outcome measure was the change in serum creatinine from baseline to 48 to 72 hours after contrast administration. Results: With regard to the primary endpoint, no significant effect of RIPC was found. CIN occurred in four patients (2 sham and 2 RIPC). A pre-defined subgroup analysis of patients with a Mehran risk score ≥11, showed a significantly reduced change in serum creatinine from baseline to 48 to 72 hours in patients allocated to the RIPC group (Δ creatinine −3.3 ± 9.8 μmol/L) compared with the sham group (Δ creatinine +17.8 ± 20.1 μmol/L). Conclusion: RIPC, as an adjunct to standard preventive measures, does not improve serum creatinine levels after contrast administration in patients at risk of CIN according to the Dutch guideline. However, the present data indicate that RIPC might have beneficial effects in patients at a high or very high risk of CIN (Mehran score ≥ 11). The RIPCIN study is registered at:http://www.controlled-trials.com/ISRCTN76496973